(untitled) - Warren, Kenneth (New York, 1975)
This is the first systematic geography of the steel industry in post-war Britain. In a detailed location analysis, which looks a qualitative as well as quantitative, evidence, the author exaamines each of the compoment factors which either promote or inhibit industrial change.
Keywords: Công nghiệp sắt thép và thương mại,Steel industry and trade